Tazkiyatu Al-Nafs Fī Sūraħ Al-Syams Min Khilāli Tafsīr Al-Qur’an Al-‘Azīm Li Ibn Kaṡīr (Tafsīran Wa Istinbāṭan): تزكية النفس في سورة الشمس من خلال تفسير القرآن العظيم لابن كثير (تفسيراً واستنباطاً) - Khalid, Muhammad Ilham; Saket, Saeed Abdullah Saeed; Tsauri, Sidiq Samsi; Rabbani, Muhammad Aqil (Civilization Research: Journal of Islamic Studies, 2022)
This study aims to uncover the meaning of self-purification in Surat al-Shams through the interpretation of the Great Qur'an by Ibn Katsir with a deduction from his interpretation of the purgatory verse, This study follows the inductive and sequential methods of the books of interpretation of the sanctified meaning especially the interpretation of the Great Qur'an by Ibn Katsir, This study aims to help awaken people to always purify themselves by understanding the word of god swt. Finally, this study proved that the meaning of praising in Surat Al-Shams according to Imam Ibn Katheer in his interpretation has two meanings. For the one who purifies himself by God, and the verb in this sense is God Almighty, i.e. He is the one who purifies the servant from polytheism with his righteousness and mercy, and God Almighty has promised him who purifies himself from uncleanness and polytheism with success.